Exploring Innovations and Security Enhancements in Android Operating System - Shakil, Muhammad Hassam; Abbasi, Muhammad Daud; Muhammad Kashif Majeed ,; Yousuf, Waleed Bin; Daniyal, Syed Muhammad; Amjad, Usama (Spectrum of Engineering Sciences, 2025)
The rapid growth of mobile phone usage over the past decade has led to increased demand for enhanced security, reliability, and performance, making mobile application security a critical concern. This study presents a freely available method for developing secure Android applications, addressing key security challenges that have not been comprehensively explored before. The research analyzes security vulnerabilities in Android applications and implements security-enhanced development strategies using various Android frameworks and techniques. Findings indicate that Android security remains a significant concern due to evolving cyber threats and increasing user dependency on mobile applications. Key security measures such as encryption, permission management, and secure coding practices are highlighted to mitigate security risks. The study also explores the real-world implementation of security-enhanced Android applications, demonstrating improved protection against unauthorized access and data breaches. Analyzing modern Android security frameworks reveals that integrating robust security measures during the development phase significantly enhances app reliability and user trust. Additionally, it discusses past security vulnerabilities in Android applications and best practices developers can adopt to prevent similar risks. By addressing these security challenges, this study provides a practical approach to developing secure applications, ensuring safer user experiences while meeting modern security demands.